2013
DOI: 10.1186/1472-6939-14-54
|View full text |Cite
|
Sign up to set email alerts
|

Depression and decision-making capacity for treatment or research: a systematic review

Abstract: BackgroundPsychiatric disorders can pose problems in the assessment of decision-making capacity (DMC). This is so particularly where psychopathology is seen as the extreme end of a dimension that includes normality. Depression is an example of such a psychiatric disorder. Four abilities (understanding, appreciating, reasoning and ability to express a choice) are commonly assessed when determining DMC in psychiatry and uncertainty exists about the extent to which depression impacts capacity to make treatment or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 29 publications
3
89
1
1
Order By: Relevance
“…Scales such as the MacCAT-CR 13 —which assess decisional capacity as it relates to appreciation, understanding, and reasoning in a research setting—have been vital to empirical studies on decision-making capacity. A recent review examining studies of decision-making capacity in depression, either in the context of treatment or research, concluded that most subjects with depression have adequate decision-making capacity, although depression appears to have the greatest impact on an individual’s ability to appreciate available options 14 . Although one study reported that depressed inpatients showed significant impairments in the abilities needed for decision-making capacity compared to inpatients with non-psychiatric illnesses, this report included subjects who had been involuntarily committed and who had other features, such as psychosis 15 .…”
Section: Issues Of Consentmentioning
confidence: 99%
“…Scales such as the MacCAT-CR 13 —which assess decisional capacity as it relates to appreciation, understanding, and reasoning in a research setting—have been vital to empirical studies on decision-making capacity. A recent review examining studies of decision-making capacity in depression, either in the context of treatment or research, concluded that most subjects with depression have adequate decision-making capacity, although depression appears to have the greatest impact on an individual’s ability to appreciate available options 14 . Although one study reported that depressed inpatients showed significant impairments in the abilities needed for decision-making capacity compared to inpatients with non-psychiatric illnesses, this report included subjects who had been involuntarily committed and who had other features, such as psychosis 15 .…”
Section: Issues Of Consentmentioning
confidence: 99%
“…Hindmarch, Hotopf, and Owen (2013) reported that “[t]he empirical studies reporting decision-making ability scores also highlighted impairment of appreciation but without evidence of strong impact” (p. 1).…”
Section: Consent To Research For People With Mental Illnessesmentioning
confidence: 99%
“…TRD is associated with increased morbidity and mortality7 8 and can negatively impact an individual's ability to participate in medical decision-making 9 10. Patients with TRD are twice as likely to be hospitalised with overall medical costs estimated at six times that of patients without TRD 5.…”
Section: Introductionmentioning
confidence: 99%